Answer:
x = 10
Step-by-step explanation:
2) -3x + 17 = -x - 3
4) 20 = 2x
1) -3x + 12 + 5 = -x -3
5) 10 = x
3) 17 = 2x - 3
<u>-3(x - 4) + 5 = -x - 3</u>
<u>-3x + 12 + 5 = -x - 3</u>
<u>-3x + 17 = -x -3</u>
<em>+3x +3x</em>
<u>17 = 2x - 3</u>
<em>+3 + 3</em>
<u>20 = 2x</u>
<u>10 = x</u>
<u />
I hope that this helps! :)
To find equivalent inequalities you have to work the inequality given.
The first step is transpose on of sides to have an expression in one side and zero in the other side:
x - 6 x + 7
--------- ≥ --------
x + 5 x + 3
=>
x - 6 x + 7
--------- - -------- ≥ 0
x + 5 x + 3
=>
(x - 6) (x + 3) - (x + 7) (x + 5)
--------------------------------------- ≥ 0
(x + 5) (x + 3)
=>
x^2 - 3x - 18 - x^2 - 12x - 35
--------------------------------------- ≥ 0
(x + 5) (x + 3)
15x + 53
- ------------------- ≥ 0
(x + 5) (x + 3)
That is an equivalent inequality. Sure you can arrange it to find many other equivalent inequalities. That is why you should include the list of choices. Anyway from this point it should be pretty straigth to arrange the terms until making the equivalent as per the options.
Answer:no because mixed numbers need atleast a one and a fraction to be mixed number but if there was a fraction then it couldnt equal two because of the 1's
Step-by-step explanation:
Hopefully this makes sense!
Answer: 12.5
Step-by-step explanation: